A study on factors that influence level of pre-retirement planning of MASkargo employees / Ahmad Rusydi Md Isa - Md Isa, Ahmad Rusydi (Faculty of Business and Management, 2015)
The purpose of this study was to determine the factors influencing level of pre-retirement planning of MASkargo employees. The variables consist of locus of control, math anxiety, and risk tolerance. The respondents were 100 employees of MASkargo Sdn Bhd. The finding showed that locus of control, math anxiety, and risk tolerance has influence on level of pre-retirement planning of MASkargo employees. All variables show significance relationship towards the factor influencing customer purchasing decision through online shopping in Malaysia.